ナンキョク セールロンダーネ サンチ シュウヘン ノ ラヒョウ イキ ニ ソンザイ スル ヨゴレ ソウ - 奈良岡, 浩; ナラオカ, ヒロシ; 矢内, 桂三; ヤナイ, ケイゾウ; 藤田, 秀二; フジタ, シュウジ; Naraoka, Hiroshi; Yanai, Keizo; Fujita, Shuji (1991)
P(論文) 第29次南極地域観測隊のあすか越冬隊はセールロンダーネ山地周辺の裸氷域における隕石探査の際に, 同じ裸氷上において汚れ層を発見採集した。汚れ層は山地周辺の裸氷域に多く存在していたが, ナンセン氷原においてその存在数が多いことが特徴であった。ろ過された試料は大部分が火山ガラスであり, 粒径や色から予備的に5種類に区分することができた。EPMA化学分析によると, 火山ガラスのSiO_2は50-70%に分布し, SiO_2-(Na_2O+K_2O)比から分析した火山ガラスの大部分は非アルカリ質であることが明らかとなった。 Dirt bands were observed on the surface of the bare ice fields around the Sør Rondane Mountains during the search for Antarctic meteorites in 1988-1989. Dirt bands were commonly distributed on the bare ice around the mountains, especially in Nansenisen. Dirt bands were collected and filtered after melting. Microscopic observation revealed that dust materials were composed mainly of volcanic glass shards. Five types of volcanic ash were preliminarily clarified with respect to the colors (black, dark gray, gray, reddish brown and pale gray) and sizes (5-50μm) of the particles. The EPMA chemical analyses indicated that the volcanic glass shards contained 50-70% SiO_2 and belonged to the nonalkaline region considering from the SiO_2-(Na_2O+K_2O) diagram. departmental bulletin paper